THE IMPACT OF ESG PRACTICES ON THE RISK PORTFOLIO OF LISTED OIL AND GAS FIRMS IN NIGERIA USING A MULTILAYERED CRITERION - Joseph Olorunfemi Akande (Gusau Journal of Accounting and Finance)
This study investigates the impact of Environmental, Social, and Governance (ESG) factors on the risk-adjusted returns of Nigerian oil and gas firms listed on the Nigerian Exchange Group (NGX) over a 11-year period (2012–2022). The study was anchored on signalling theory. Utilizing a correlational research design, data was collected from eight firms meeting inclusion criteria, focusing on ESG scores as independent variables, with Firm Size as a control variable, and risk-adjusted returns as the dependent variable. Diagnostic tests ensured adherence to Best Linear Unbiased Estimator (BLUE) assumptions. Employing both Ordinary Least Squares (OLS) and Two-Stage Least Squares (2SLS) regression techniques, the study addresses potential endogeneity, using industry norms as an instrumental variable (IV) in the 2SLS model. Findings indicate significant, positive relationships between ESG factors and risk-adjusted returns, emphasizing the financial viability of sustainable practices in a sector known for environmental and social risks. Hence, to strengthen financial and operational resilience, Nigerian oil and gas firms are encouraged to prioritize robust environmental practices, including emission reduction, waste management, and prevention of oil spills. Given the social challenges in regions like the Niger Delta, firms should focus on building trust and maintaining positive relationships with local communities through initiatives in healthcare, education, and infrastructure. This study provides key insights into how ESG engagement in Nigerian oil and gas firms may influence firm stability, resilience, and investor confidence, underscoring the role of signalling theory in linking ESG performance to enhanced corporate valuation.